2017
DOI: 10.3171/2016.9.peds16210
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of atrial diameter and frontooccipital horn ratio with ventricle size in fetal ventriculomegaly

Abstract: OBJECTIVE Fetal ventriculomegaly (FV), or enlarged cerebral ventricles in utero, is defined in fetal studies as an atrial diameter (AD) greater than 10 mm. In postnatal studies, the frontooccipital horn ratio (FOHR) is commonly used as a proxy for ventricle size (VS); however, its role in FV has not been assessed. Using image analysis techniques to quantify VS on fetal MR images, authors of the present study examined correlations between linear measures (AD and FOHR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Our findings in terms of the relationship between AD and volume in VM group are consistent with those of a previous study. [27] The equations acquired in the present study suggest that the lateral ventricular volume could be estimated using AD. To the best of our knowledge, this is the first study to evaluate the association between linear measurement and volume of the normal LV.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings in terms of the relationship between AD and volume in VM group are consistent with those of a previous study. [27] The equations acquired in the present study suggest that the lateral ventricular volume could be estimated using AD. To the best of our knowledge, this is the first study to evaluate the association between linear measurement and volume of the normal LV.…”
Section: Discussionmentioning
confidence: 72%
“…The expansion of the ventricles was especially pronunced in the body of the lateral ventricles. Other studies in posthemorrhagic hydrocephalus and fetal ventriculomegaly have reported that the body dilates to a greater extent than other ventricle regions, such as the frontal horn [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Commonly used linear measures were obtained using measurement tools in EasyViz software (Medical Insight). Atrial diameter was measured in the axial plane on a single section at the level of the atria of the lateral ventricles and the glomus of the choroid plexus 14 ( Figure 1A). The fronto-occipital horn ratio (FOHR) was calculated using the same axial section used to measure atrial diameter; it is the mean of the maximum frontal and occipital horn diameters divided by the biparietal diameter [(a + c)/2b] ( Figure 1A).…”
Section: Image Acquisition and Analysismentioning
confidence: 99%